Climate change policy and power sector reform in Mexico under the 'golden age of gas' - José Maria Valenzuela; Isabel Studer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Mexico's low-carbon technology perspectives show lack of coherence with the rising ambition in climate change commitments, for which Mexico is internationally praised. The comparison of two recent energy reforms, corresponding to two administrations, explains this lack of coherence by, on the one hand, the permanence of a strong climate institutional framework devised as a means to increase energy security and, on the other hand, the political commitment to reduce electricity tariffs through the access to low-priced gas in North America. This paper underscores the political economy trade-offs between the need for a strong climate commitment that provides a stable long-term energy transition pathway and the political and economic short-term benefits derived from low electricity tariffs.
Keywords: L98; O33; P48; Q48; 330; power sector; climate change; renewable energy; natural gas; market reform; energy transition